Temperature compensated power detector towards power consumption optimization in 5G devices. (February 2022) - Alaji, Issa; Okada, Etienne; Gloria, Daniel; Ducournau, Guillaume; Gaquière, Christophe
Abstract: The design and characterization of a real-time temperature compensated power detector are presented in this article. The working frequency band of the detector is (40.5–42.5) GHz, dedicated to optimize power consumption in 5G devices. A novel and simple technique is proposed in this work in order to compensate the variation of the voltage sensitivity value (γ) with temperature. This technique is based on adding a passive circuit which acts as a resistor with positive temperature coefficient, which absorbs less of input power at higher temperatures. As a result, the measurements show that the degradation of sensitivity value with temperature is suppressed by more than 55%, and therefore, this value -at the frequency 41 GHz-has a small variation (γ = 1530 V/W±6%) over the temperature range (20–100)°C. Compared to recent published works, the proposed detector circuit is quite simple with no power consumption. In addition, it is operated at higher frequencies in order to be suitable for 5G applications.